Child Sexual Abuse and Depression in Late Life for Men: A Population-Based, Longitudinal Analysis. (27th September 2017) - Easton, Scott D; Kong, Jooyoung; Gregas, Matt C; Shen, Ce; Shafer, Kevin
Abstract: Objective: Research investigating long-term effects of childhood sexual abuse (CSA) on mental health for men is vastly underdeveloped. This study strengthened the knowledge base by examining: (a) long-term trajectories of depressive symptoms for men with and without a history of CSA, and (b) moderating effects of social support over time. Method: We analyzed multiple waves of data from the Wisconsin Longitudinal Study. The sample ( N = 2, 451) consisted of men with histories of CSA and a stratified, randomly sampled comparison group. Growth curve modeling was employed for analyses. Results: After controlling for demographic, parental, and health factors, men with CSA histories had greater depressive symptoms than those with no history of CSA. For both groups, depressive symptoms decreased over time; slope patterns did not differ. We found a significant moderating effect of social support on the relationship between CSA and depressive symptoms. Discussion: This innovative, population-based, longitudinal study demonstrated that CSA can undermine mental health for men across the life span and into old age. Social support appears to mitigate these deleterious effects. In early, middle, and late adulthood, practitioners should assess for CSA and strengthen support resources for male survivors.